Adoção do International Financial Reporting Standards no Brasil: um estudo setorial de value relevance - Vaz, Janderson Martins (2018)
Considering the context of globalization and trying to establish information that would meet the demands of society, accounting standards regulators have established a harmonized standard of accounting principles resulting in the International Financial Reporting Standards (IFRS). In order to contribute to the debate on the harmonization of accounting standards, especially since the adoption of IFRS in Brazil, based on the theory of value relevance and including sectoral information in the analysis, this study verified the effects of adopting the IFRS on the relevance of accounting information of Brazilian companies that trade in B3. The sample was grouped in economic sectors using the sector classification of the Economática® database. Factorial scores were obtained by factorial analysis representing the economic sectors. The Ohlson model (1995) was used to identify the value relevance of accounting information in each economic sector. Additionally, the performance of value relevance in the economic sectors was verified during the phases of harmonization of the Brazilian GAAPs to the IFRS identified in the theoretical framework. Two dichotomous variables representing distinct phases of the accounting harmonization process in Brazil were included in the model. Data were analyzed using the statistical technique of multivariate regression analysis of time series by Autoregressive with Moving Average and Exogenous Inputs (ARMAX) models. The results demonstrated the existence of different effects on the value relevance of the accounting information between the sectors. The IFRS harmonization period had significant effects on all sectors of the sample, while the full IFRS period did not show significant effects in five sectors, showing that the IFRS harmonization process had heterogeneous effects among the nine sectors analyzed.